Geographical variation in the golden-striped salamander, Chioglossa lusitanica Bocage, 1864 and the description of a newly recognized subspecies - Arntzen, Jan W.; Groenenberg, Dick S. J.; Alexandrino, Joao; Ferrand, Nuno; Sequeira, Fernando (Taylor & Francis Ltd, 2007)
Morphological and genetic data for the Iberian golden- striped salamander, Chioglossa lusitanica, demonstrate the existence of two groups with southern and northern ranges, connected by a zone of intergradation in central Portugal. Because reproductive isolation between them is incomplete we consider the groups to be subspecies. The type locality of C. lusitanica ( Bucaco near Lousa) is situated inside the mixed zone. This necessitates identification of the nominotypical subspecies. We sequenced a fragment of mitochondrial DNA from one of the species' syntypes and we determined what position over a latitudinal transect maximizes the morphological discrimination between the groups. Both approaches indicate that C. lusitanica from Bucaco represents the southern subspecies. A new subspecies of C. lusitanica is described from a northern locality ( Valongo near Porto in northwestern Portugal). A lectotype is designated for Chioglossa lusitanica.
Keywords: ancient DNA; Chioglossa lusitanica; cytochrome-b; geographic variation; morphometrics; new subspecies; Portugal; salamander; Urodela